PENANGANAN PERKARA TERHADAP ANAK PELAKU PELECEHAN SEKSUAL TERHADAP ANAK (Studi Penelitian di Kepolisian Resort Kota Lhokseumawe) - Marpaung, Suci Ramanda; Nur, Muhammad; Yusrizal, Yusrizal (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2024)
AbstractThe high number of children committing sexual harassment is due to the ease with which they can access pornographic websites. This research aims to understand and explain the legal process for criminal acts of theft committed by children and the application of criminal law against child perpetrators of sexual harassment. The research method used is the empirical juridical method. The results of the research regarding the handling process of cases involving child perpetrators of sexual harassment show that the police, authorized by Law Number 8 of 1981 on Criminal Procedure, immediately conduct investigations, inquiries, and even arrests, searches, and detentions of perpetrators once sufficient evidence is found. Even though the perpetrators are minors, the law enforcement process must be carried out. For child perpetrators of sexual harassment against minors, the law enforcement process, starting from investigation, inquiry, prosecution, and trial, is conducted in accordance with Law Number 11 of 2012.Keywords : Handling, Crime, Sexual Harassment, Child